Mesenchymal stromal cells protect hepatocytes from lipotoxicity through alleviation of endoplasmic reticulum stress by restoring SERCA activity. Issue 6 (16th February 2021) - Li, Linzhao; Zeng, Xin; Liu, Zhenzhen; Chen, Xuanming; Li, Lan; Luo, Ruixi; Liu, Xiaohong; Zhang, Jie; Liu, Jingping; Lu, Yanrong; Cheng, Jingqiu; Chen, Younan
Abstract: The aim of this study was to investigate how mesenchymal stromal cells (MSCs) modulate metabolic balance and attenuate hepatic lipotoxicity in the context of non‐alcoholic fatty liver disease (NAFLD). In vivo, male SD rats were fed with high‐fat diet (HFD) to develop NAFLD; then, they were treated twice by intravenous injections of rat bone marrow MSCs. In vitro, HepG2 cells were cocultured with MSCs by transwell and exposed to palmitic acid (PA) for 24 hours. The endoplasmic reticulum (ER) stressor thapsigargin and sarco/ER Ca 2+ ‐ATPase (SERCA2)–specific siRNA were used to explore the regulation of ER stress by MSCs. We found that MSC administration improved hepatic steatosis, restored systemic hepatic lipid and glucose homeostasis, and inhibited hepatic ER stress in HFD‐fed rats. In hepatocytes, MSCs effectively alleviated the cellular lipotoxicity. Particularly, MSCs remarkably ameliorated the ER stress and intracellular calcium homeostasis induced by either PA or thapsigargin in HepG2 cells. Additionally, long‐term HFD or PA stimulation would activate pyroptosis in hepatocytes, which may contribute to the cell death and liver dysfunction during the process of NAFLD, and MSC treatment effectively ameliorates these deleterious effects. SERCA2 silencing obviously abolished the ability of MSCs against the PA‐induced lipotoxicity. Conclusively, our study demonstrated that MSCs were able to ameliorate liver lipotoxicity and metabolic disturbance in the context of NAFLD, in which the regulation of ER stress and the calcium homeostasis via SERCA has played a key role.